Academic free speech or right-wing grievance?. (8th March 2023) - Herbert, John M.
Abstract : A counterpoint to the idea that "academic freedom" should protect bigotry, an evidence-driven case for diversity, and a call to fight White, cisgender, heterosexual male supremacy within the scientific enterprise. Abstract : A vociferous group of scientists is presently articulating the idea that academic freedom is under attack from within academia. Examples of supposed suppression of free expression often involve diversity, equity, and inclusivity efforts by universities, especially diversity considerations in faculty hiring, but also include examples where academics have been censured or disciplined for racist, sexist, or transphobic speech. Free-speech libertarians advocate for a definition of academic freedom in which no remark is inflammatory enough to warrant consequences, even when such remarks are unsupported by (or unconnected to) academic scholarship. The present work offers an evidence-driven analysis to support the contention that this misconstrues the role of academic freedom, which is not imperiled by the notion that there should be social or professional consequences for some antisocial or abusive speech. Troublingly, the rhetoric employed by self-proclaimed defenders of free speech often bears striking similarities to the language of resentment that is used in contemporary political discourse to express right-wing grievance that is centered around White heterosexual male identity. Phrases such as "cancel culture" and "woke ideology", used as pejoratives, are favored not only by free-speech hardliners but also by politicians who are working to dismantle the academic tenure system in the U.S. Misappropriated terms such as "critical race theory" are used to defend new laws that restrict classroom and workplace discussion of race and gender identity. The present work argues that those who wish to have an honest debate about the limits around freedom of speech need to engage that conversation in a manner that avoids resonance with the language of White (heterosexual, cisgender male) supremacy, lest their arguments provide intellectual cover to those who would attack historically marginalized communities. Suggestions for countering regressive academic culture are provided, along with a data-driven discussion of diversity considerations in faculty hiring. An emergent theme is that the academic status quo supports White male supremacy, therefore complacency by tenured academics will perpetuate that situation.